Factors influencing sustainable indigenous tourism among the Mah Meri community in Carey Island, Malaysia - Kunasekaran, Puvaneswaran (2014)
This study is aimed to determine the factors that influence the indigenous community to attain sustainable tourism practice. The study area which is selected is Kampung Sungai Bumbon, Carey Island in Selangor. This village also known as Mah Meri Cultural Village (MMCV) is a well established indigenous tourism destination in Malaysia occupied by the Mah Meri community. An initial investigation done in the village provided clearer understanding on the issues of resource scarcity, empowerment, participation and sustainability faced by the community. To answer the research questions, a mixed method study has been employed where qualitative and quantitative methods are combined. The first part of the study is treated as an inductive approach, detailing data collected through in-depth interviews. The naturalistic inquiry study revealed some factors, which were already found by previous researchers, and some new factors emerged. The interview data which had been transcribed and translated was analyzed using discourse analysis technique. Discourse analysis revealed the five community resources that are important to the Mah Meri community to sustain their tourism practice. The five community resources are cultural resources, human resources, financial resources, infrastructure resources and natural resources. Cultural resources have been the most important asset of the Mah Meri community to run tourism successfully. The community also revealed that the scarcity of the natural resources especially Nyireh Batu is a big threat for sustainable tourism. Next, the analyzed qualitative data was put under deduction process using quantitative procedures. In inferential analysis, the results from analysis on the variables using statistical techniques, such as correlation analysis and multiple regressions analysis were produced. After finding that all the independent variables are correlated with the dependent variable, multiple regression analysis was conducted. The findings of the multiple regressions show that six variables are significant in predicting the sustainable indigenous tourism; cultural resources, participation, self-reliance, empowerment, capacity building and human resources. The result of the study also does not contradict the social exchange theory, which says that the people who get benefit from tourism,support tourism. The indigenous people who involved directly in tourism tended to have positive perceptions towards indigenous tourism, because they directly receive economic benefits from tourism. Apart from that, the other villagers who are not directly involved in tourism are not averse to tourism. Although they barely get any income from tourism, they are still in favor of tourism mainly for impact on cultural and environmental sustainability derived by tourism activities. Thus, although this study supports the social exchange theory, the outcome shows that the non-participants of tourism in Kampung Sungai Bumbon are also supporting tourism but their support is not as high as the direct participants (weavers, wood carvers and dancers). The finding also proves that the community is not practicing individual development but supports people involved in tourism for the betterment of the whole village. This argument is an important contribution to the social exchange theory which heavily focused on the economic benefit and community development and neglecting the socio-cultural and environmental perspectives.